Transforming Education: A PBL Framework for Fostering Student Understanding and Communication Skills in the Face of Climate Change and Global Warming - Merry Novia; Asrizal Asrizal (STAI Hubbulwathan Duri, 2023)
Learning in an independent curriculum involves independent conditions for fulfilling objectives, methods, materials, and learning evaluations for both teachers and students. The preliminary research students' conceptual understanding results and communication skills are still low. The solution to the problem is the integrated Problem Based Learning (PBL) model E-Student Worksheet (E-SWS) is the solution to this problem. This study aims to look at the effect of climate change E-SWS on global warming integrated with the PBL model to support the improvement of the process for conceptual understanding and skills for communicating with students. This research is included in the quasi-experimental research through the Posttest-Only control design. The research instrument for conceptual understanding is measured through a final test, and aspects of communication skills are measured through scientific work in the form of written ideas. Based on the data analysis of learning outcomes aspects of conceptual understanding and communication skills with successive averages of 88.19 and 80.20, the research work hypothesis is accepted. The research results implication is that teachers must construct students through integrated PBL models and E-SWS teaching materials. The research results reached the conclusion that student learning outcomes using the climate change E-SWS in integrated global warming PBL models were significantly higher than the teaching materials in schools.